Tip-to-base conduit widening remains consistent across cambial age and climates in Fagus sylvatica L - Rita, Angelo; Pericolo, Osvaldo; Tumajer, Jan; Ripullone, Francesco; Gentilesca, Tiziana; Saracino, Antonio; Borghetti, Marco (Tree physiology, 2024)
Water transport, mechanical support and storage are the vital functions provided by the xylem. These functions are carried out by different cells, exhibiting significant anatomical variation not only within species but also within individual trees. In this study, we used a comprehensive dataset to investigate the consistency of predicted hydraulic vessel diameter widening values in relation to the distance from the tree apex, represented by the relationship Dh ∝ Lβ (where Dh is the hydraulic vessel diameter, L the distance from the stem apex and β the scaling exponent). Our analysis involved 10 Fagus sylvatica L. trees sampled at two distinct sites in the Italian Apennines. Our results strongly emphasize that vessel diameter follows a predictable pattern with the distance from the stem apex and β ~ 0.20 remains consistent across cambial age and climates. This finding supports the hypothesis that trees do not alter their axial configuration represented by scaling of vessel diameter to compensate for hydraulic limitations imposed by tree height during growth. The study further indicates that within-tree variability significantly contributes to the overall variance of the vessel diameter-stem length exponent. Understanding the factors that contribute to the intraindividual variability in the widening exponent is essential, particularly in relation to interspecific responses and adaptations to drought stress.
Keywords: Cambium; Xylem; vessels; kambium; hydraulic; Italy; Plant Stems; Itálie; Fagus; xylem traits; stromy; voda; Water; xylém; podnebí; buk (rod); architecture; diffuse-porous; Climate; Trees; quantitative wood anatomy; stonky rostlin; allometry